2005
DOI: 10.1590/s1807-59322005000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Aquatic Versus Non-Aquatic Respiratory Exercise Program on the Respiratory Muscle Strength in Healthy Aged Persons

Abstract: Aging of the worldwide population is a concern of most governmental entities, spanning practically all areas of prevention and rehabilitation. Aging leads to physiological alterations that result in adverse social and financial effects. There is a trend to emphasize prevention, which is less expensive and socially more desirable than therapeutic intervention. PURPOSE: To assess the effect of a program of aquatic versus non-aquatic respiratory exercises on respiratory muscle strength in healthy aged persons.MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
1
18
1
9
Order By: Relevance
“…Typically, we would expect lung function to improve in both healthy and diseased populations with aquatic exercise (Ide, Belini, & Caromano, 2005;Silvers, Rutledge, & Dolny, 2007;Wardell & Isbister, 2000). Participants within the current study had a baseline FEV 1.0 /FVC value of 98% (SD = 8.91%), and a postexercise value of 98.5% (SD = 8.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, we would expect lung function to improve in both healthy and diseased populations with aquatic exercise (Ide, Belini, & Caromano, 2005;Silvers, Rutledge, & Dolny, 2007;Wardell & Isbister, 2000). Participants within the current study had a baseline FEV 1.0 /FVC value of 98% (SD = 8.91%), and a postexercise value of 98.5% (SD = 8.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Ide et al 10 compared aquatic vs. non-aquatic respiratory training programs on muscle strength of 81 healthy senior persons, and concluded that aquatic respiratory exercise improves the inspiratory but not expiratory muscle strength.…”
Section: Editorialmentioning
confidence: 99%
“…As the hydrostatic pressure increases, the vital capacity (VC), functional residual capacity (FRC) and expiratory reserve volume (ERV) decreases thanks to the diaphragm displacement in the cephalic direction and to the increase in the work of expiratory muscle 12,13 . The respiratory system changes because of the blood displacement from peripheral regions to the central region of the chest, in addition to the hydrostatic pressure on the rib cage, thereby increasing the respiratory work 14,15 . The aim of this study is to analyze and compare the respiratory muscle strength in healthy individuals, exercised in soil and in the pool, with the chest immersed in water.…”
Section: Introductionmentioning
confidence: 99%